MICRO-GEOPOLITICAL SEMIOTICS OF CENTRAL ASIA: “CROSSROADS” AND “BRIDGES” - TOLIPOV, Farkhod (CENTRAL ASIA AND THE CAUCASUS, 2015)
The author analyzes a highly specific geopolitical phenomenon—geopolitical self-identification of the Central Asian countries with the help of geographic images, symbols, and signs used to prove their importance on the international arena and at the regional level in particular. In his analysis the author uses a constructivist approach to the efforts to fit several geographic descriptions into a geopolitical context combined, to a certain extent, with a realistic approach expressed by the term “geopolitical semiotics.”